Learning Disabilities An International Perspective - Ryan, Carolyn S. (IntechOpen, 2017)
Learning disabilities are conditions that are associated with difficulties in knowledge and skill acquisition to the level expected of same-age peers. The current book is an international examination of assessment methods, preventative measures, intervention, and research with those individuals with learning disabilities obtained from authors in the United States of America, Europe, Asia, and Africa.